2014
DOI: 10.1007/s11255-014-0788-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave lithotripsy under sedoanalgesia for treatment of kidney stones in infants: a single-center experience with 102 cases

Abstract: SWL therapy under sedoanalgesia is a safe and efficient treatment modality that can be administered with low complication rates and high stone-free rates in the treatment of renal stones in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…[25][26][27][28] Very few studies have examined the risk of hypertension developing after SWL in children, and appear to rule out this possibility. 25,29 As for ureteroscopic lithotripsy (URSL), one study on single-kidney patients compared URSL with SWL and found no differences in terms of subsequent renal function. 30 Multiple URSL procedures did not alter the long-term GFR in stone-forming patients with CKD stages 2-3(Suppl.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[25][26][27][28] Very few studies have examined the risk of hypertension developing after SWL in children, and appear to rule out this possibility. 25,29 As for ureteroscopic lithotripsy (URSL), one study on single-kidney patients compared URSL with SWL and found no differences in terms of subsequent renal function. 30 Multiple URSL procedures did not alter the long-term GFR in stone-forming patients with CKD stages 2-3(Suppl.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Çocuklarda SWL uygulamaları sırasında anestezi gereksinimi de; başka bir sorundur. Ancak son yıllarda geliştirilen fokus alanı daha dar olan litotriptörlerle genel anestezi gerekmeksizin sadece sedoanaljezi yapılarak SWL etkin şekilde kullanılabilmektedir (21,27). Yeni jenerasyon makinelerde SWL infantlarda bile sedo-analjezi ile başarılı bir şekilde uygulanmaktadır.…”
Section: çOcuklukunclassified
“…Bir çalışmada Adanur ve ark. 'ları infantlarda sedo-analjezi için pentothalsodium 3-4 mg/kg ve fentanyl 1-2 µg/kg dozlarda kullanıldığını bildirmişlerdir (27). Daha büyük çocuklarda ise; (<5 yaş) kliniğimizde propofol 1-2 mg/kg ve fentanyl 1-2 µg/kg kombinasyonu kullanılmaktadır (21 Modifiye etkinlik değeri (EQmod)= Taştan arınmış hasta % -Küratif yardımcı tedaviler % %100+Tekrar taş kırma %+Taş kırma öncesi yardımcı tedaviler% + Taş kırma sonrası adjuvan tedaviler % kullanılan klinik olarak önemsiz rezidüel fragman teriminin çocuklarda SWL sonrası 3 mm ve daha küçük taş fragmanları için kullanılması uygun görülmemiştir.…”
Section: çOcuklukunclassified